2012
DOI: 10.1371/journal.pone.0033331
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Pulmonary Artery Stiffness in Pulmonary Arterial Hypertension: In Vivo Study with Intravascular Ultrasound

Abstract: BackgroundThere is increasing recognition that pulmonary artery stiffness is an important determinant of right ventricular (RV) afterload in pulmonary arterial hypertension (PAH). We used intravascular ultrasound (IVUS) to evaluate the mechanical properties of the elastic pulmonary arteries (PA) in subjects with PAH, and assessed the effects of PAH-specific therapy on indices of arterial stiffness.MethodUsing IVUS and simultaneous right heart catheterisation, 20 pulmonary segments in 8 PAH subjects and 12 pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 32 publications
7
24
0
Order By: Relevance
“…MDCT-derived pulsatility fairly agrees with that measured by IVU and MRI [11][12][13][14][15][16][17][18][19][20][21], indicating a mean pulsatility of 20% ± 5%. The pulsatility significantly diminishes in patients affected by PH, because of arterial remodelling leading to arterial stiffness [16,17].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…MDCT-derived pulsatility fairly agrees with that measured by IVU and MRI [11][12][13][14][15][16][17][18][19][20][21], indicating a mean pulsatility of 20% ± 5%. The pulsatility significantly diminishes in patients affected by PH, because of arterial remodelling leading to arterial stiffness [16,17].…”
Section: Discussionsupporting
confidence: 65%
“…The assessment of pulsatility (Puls) of pulmonary artery (PA) in PH looks like a promising tool, since it looks related to severity, progression of disease, functional capacity, prognosis, and survival [6][7][8][9]. The invasive right heart catheterization (RHC) is the gold standard for the diagnosis of PH, and the assessment of reversibility of PH with vasodilators, the measure of Puls by intravascular ultrasound (IVU) [10][11][12][13][14]. The noninvasive cardiac echocardiography (US) allows the measurement of the pulmonary artery dimensions, the right ventriculare shape, the ejection fraction, and the noninvasive estimation of the systolic pulmonary artery pressure [15][16][17][18], but the applicability of US in patients affected by COPD is limited because of the reduced acoustic window [15], due to pulmonary hyperinflation.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial compliance decreases when mPAP increases, and this pressure-dependence of pulmonary arterial wall stiffness (1/C) is due to the nonlinear stress-strain relationship [48,49]. In other words, a decrease in total arterial compliance can result from an increase in mPAP without a true change in the elastic properties of the pulmonary arterial wall.…”
Section: Pulmonary Vascular Resistancementioning
confidence: 99%
“…In other words, a decrease in total arterial compliance can result from an increase in mPAP without a true change in the elastic properties of the pulmonary arterial wall. Arterial compliance can also decrease when the pulmonary arterial wall stiffens due to a decreased elastin/collagen ratio as a result of vascular remodelling [48,49].…”
Section: Pulmonary Vascular Resistancementioning
confidence: 99%
“…PVC measures how much the pulmonary arteriolar tree will dilate with each contraction of the right ventricle and reflects pulsatile RV afterload. Lau et al [12] used intravascular ultrasound (IVUS) to evaluate the properties of the elastic pulmonary arteries in eight PAH patients, and found that increased stiffness occurs in the proximal elastic pulmonary artery and that there was an inverse association between mPAP and compliance. Higher PVC may reflect less remodeling in pulmonary elastic arteries.…”
Section: Discussionmentioning
confidence: 99%